The Effect of Exercises Using Maximum Strength Assisting Training Apparatus On Some Working Muscles' Electric Activity During Bench Press For Physical Strength Athletes Of Baghdad Clubs - Abdul Reda, Ahmed; Adeeb, Ghassan (Journal of Physical Education, 2019)
Physical strength athletes need to improve their maximum strength continuously to break the records and achieve their aims. The problem of the research lies in maximum strength weakness thus the researchers designed a training apparatus to address this problem. A set of exercises were designed to be used on this apparatus hypothesizing that regular training on the apparatus have positive effects on the electric activity of the chest muscles due to the adaptation to this range of motion.